Microgel assisted Lab-on-Fiber Optrode. Issue 1 (December 2017) - Aliberti, A.; Ricciardi, A.; Giaquinto, M.; Micco, A.; Bobeico, E.; La Ferrara, V.; Ruvo, M.; Cutolo, A.; Cusano, A.
Abstract Precision medicine is continuously demanding for novel point of care systems, potentially exploitable also forin-vivo analysis. Biosensing probes based on Lab-On-Fiber Technology have been recently developed to meet these challenges. However, devices exploiting standard label-free approaches (based on ligand/target molecule interaction) suffer from low sensitivity in all cases where the detection of small molecules at low concentrations is needed. Here we report on a platform developed through the combination of Lab-On-Fiber probes with microgels, which are directly integrated onto the resonant plasmonic nanostructure realized on the fiber tip. In response to binding events, the microgel network concentrates the target molecule and amplifies the optical response, leading to remarkable sensitivity enhancement. Moreover, by acting on the microgel degrees of freedom such as concentration and operating temperature, it is possible to control the limit of detection, tune the working range as well as the response time of the probe. These unique characteristics pave the way for advanced label-free biosensing platforms, suitably reconfigurable depending on the specific application.